735 CLINICAL EFFICACY OF CEREBRAL EMBOLIC PROTECTION IN TRANSFEMORAL TAVI PROCEDURE. (15th December 2022) - Mainardi, Andrea; Nicolini, Elisa; Andreaggi, Stefano; Fabroni, Margherita; Maolo, Alessandro; Mariottini, Margherita; Pesarini, Gabriele; Scarsini, Roberto; Mammone, Concetta; Ribichini, Flavio; Piva, Tommaso; Pighi, Michele
Abstract: Background: Although in the context of Transcatheter Aortic Valve Implantation (TAVI) technological improvements, refinements in technique and increased operator experience have led to progressive reduction in most complications, periprocedural neurological ischemic event (stroke and TIA) continues to occur in up to 2% of patients undergoing TAVI. Many of these are attributed to embolic events during the procedure and can lead to potentially devastating consequences. Cerebral Embolic Protection (CEP) devices have been developed to mitigate this risk. Data regarding the clinical efficacy of these devices in preventing neurological events in TAVI are conflicting. The aim of the present study is to investigate the impact of CEP on clinical neurological events in TAVI. Methods: We performed a multicentric retrospective observational case-control study to evaluate the rate of periprocedural clinical neurological ischemic event in patients undergoing transfemoral TAVI with or without using CEP (Sentinel, Boston Scientific) during the procedure. Patients were consecutively enrolled between January 2018 and December 2021 by two tertiary centers (Verona and Ancona). A total population of 1042 patients were enrolled. The primary endpoint was the rate of a periprocedural clinical neurological ischemic event. The secondary was a composite endpoint: in-hospital death, periprocedural major vascular complication and periprocedural major bleeding. Clinical events at 30-day follow-up were evaluated (death, clinical neurological ischemic event, vascular complications, major bleeding). In consideration of the retrospective study design, we performed a propensity match analysis to account for differences in the baseline characteristics of patients in the two enrolling centers. Results: The overall population comprised patients who underwent TAVI without using CEP (No-CEP group, n=581) and with CEP (CEP group, n=461). The propensity match analysis yielded a final population of 922 patients: 461 patients in the No-CEP group and 461 patients in the CEP group. There were no differences in baseline characteristics between the groups. Primary endpoint occurred in 8 (0, 9%) patients overall, 3 (0, 7%) patients in the No-CEP group and in 5 (1, 1%) patients in CEP group (p=0, 725). There were no differences in secondary endpoint: 25 (5, 4) patients in No-CEP group and 20 (4, 3%) in CEP group (p=0, 541). In particular: in-hospital death (0, 7% vs 1, 3%, p=0, 506), periprocedural major vascular complications (2, 0% vs 0, 7%, p=0, 143), periprocedural major bleeding (5, 0% vs 3, 0%, p=0, 179). No differences were observed in 30-days outcomes: death (0, 0% vs 0, 9%, p=0, 131), clinical neurological ischemic events (0, 8% vs 0, 7%, p=1), vascular complications (0, 3% vs 0, 0%, p=0, 450), major bleeding (0, 8% vs 0, 7%, p=1). The multiple logistic regression performed to estimate the effect of CEP on the primary endpoint showed Euroscore II (OR, 1.10; 95% CI, 1.00–1.19; P =0.028) and predilatation (OR, 4.84; 95% CI, 1.21–21.64; P =0.028) was associated with an increase in primary endpoint after TAVI, while CEP and valve type did not contribute significantly. Conclusions: This study suggests that using CEP devices during transfemoral TAVI is safe and does not increase vascular complications, although it does not impact the rate of periprocedural clinical neurological ischemic events.